Validation of the Expressions of Moral Injury Scale‐Military version‐Short Form. (22nd November 2019) - Currier, Joseph M.; Isaak, Steven L.; McDermott, Ryon C.
Abstract : Military personnel may encounter morally injurious events that lead to emotional, social, and spiritual suffering that transcend and/or overlap with mental health diagnoses (e.g., post‐traumatic stress disorder [PTSD]). Advancement of scientific research and potential clinical innovation for moral injury (MI) requires a diversity of measurement approaches. Drawing on results from the bifactor model in Currier et al.'s (2017) psychometric evaluation of the Expressions of Moral Injury Scale‐Military version (EMIS‐M), this study validated a four‐item short form of the instrument with two samples of veterans with a history of war‐zone service. Namely, despite the reduced number of items, the EMIS‐M‐Short Form (SF) yielded favourable internal consistency and comparable levels of convergent validity with theoretically related constructs (e.g., PTSD and struggles with morality and ultimate meaning) as the full‐length version. Notwithstanding the possible utility of distinguishing between self‐ and other‐directed forms of MI, factor analytic results further revealed that the EMIS‐M‐SF was best conceptualized with a unidimensional factorial model that might allow for a general assessment of MI‐related outcomes. Overall, these initial results suggest that the EMIS‐M‐SF may hold promise as a short, reliable, and valid assessment of overall outcomes related to a possible MI.